On the identity of Geophilus armatus Silvestri, 1895, a junior synonym of Plateurytion tenebrosus (Meinert, 1886), and other Neotropical members of the genus Plateurytion Attems, 1909, including Plateurytion mauryi, n. sp. from the Andes of Argentina (Myriapoda: Chilopoda: Geophilomorpha) - Pereira, Luis Alberto (2008)
The type specimens (male and female “Cotypi”) of Geophilus armatus Silvestri, 1895 (here designated as lectotype and paralectotype respectively), and the lectotype and paralectotypes of Geophilus tenebrosus Meinert, 1886 [currently Plateurytion tenebrosus (Meinert, 1886)] were compared morphologically, and all specimens are considered conspecifi c. Consequently, G. armatus is here designated as a new junior synonym of P. tenebrosus. A redescription of the species is given, based on the study of numerous additional specimens from Argentina and a few from Uruguay, including new data on morphological characters and their intraspecifi c variation, as well as new distributional records which expand signifi cantly our knowledge of the geographical range of the species. Plateurytion mauryi n. sp. (Chilopoda: Geophilomorpha: Geophilidae) is here described and illustrated from a single female specimen collected in Argentina (Mendoza province: Las Heras departement: Puente del Inca) at ca. 2933 m a.s.l., in the eastern slope of the Andes (within the Altoandina biogeographic province). Th e new species is characterized by having the coxal organs grouped in clusters (two in each coxopleuron of the last leg-bearing segment), this character being shared by two other Neotropical species of the genus, i.e., P. lethifer (Crabill, 1968) and P. yungarun (Pereira, 2005), from the Yungas of Peru and Argentina respectively, to which it seems to be closely related and with which it is accordingly compared in detail. New diagnoses for these latter species are also given.